0583 Obstructive Sleep Apnea Severity And Cancer Survival. (12th April 2019) - Sillah, Arthur; Watson, Nathaniel F; Gozal, David; Phipps, Amanda I
Abstract: Introduction: Obstructive sleep apnea (OSA) afflicts an estimated 25 million Americans. In vitro and animal models suggest that OSA related intermittent hypoxia and fragmented sleep contributes to increased cancer risk and poorer prognosis. Presently, little is known regarding the relationship between OSA severity and cancer mortality. We compared mortality risk in cancer patients according to clinically diagnosed OSA severity. Methods: We identified a cohort of adults with a diagnosis of OSA between 2005-2013 within a clinical system in the Seattle-Puget Sound region. We linked this cohort to a population-based cancer registry serving the same region to identify incident cancers and all-cause mortality between 2005-2015 following OSA diagnosis. The following five OSA severity indicators were evaluated as continuous or categorical variables in relation to cancer survival: apnea-hypopnea index (AHI), hypoxemic burden (Tsat < 90), oxygen desaturation index (ODI3%), oxygen saturation nadir (lowest_satO2) and arousal index. Cox proportional hazards regression was used to calculate hazard ratios (HR) and 95% confidence interval (CI) for the association of OSA severity indices with all-cause cancer mortality, adjusting for age, gender, body mass index and smoking. Results: Study population included 328 OSA patients with a cancer diagnosis, among whom 51 deaths occurred within a median follow-up of 666 days (IQR: 259, 1, 324) after cancer diagnosis. Information regarding OSA severity indicators were missing for ~30% of cohort. Compared with individuals in the lowest AHI category (>5-14.9), indicating mild OSA, the adjusted HR (95% CI) for cancer mortality associated with having moderate (15-29.9), severe (30+) OSA were 0.31 (0.07, 1.40), 0.71 (0.26, 1.92) respectively. With respect to the lowest Tsat<90 category (>1.2), indicating mild OSA, the adjusted HR associated with having moderate (<1.2-12.9), severe (13+) OSA were 0.89 (0.32, 2.47), 1.59 (0.67, 3.75) respectively. Associations of cancer mortality with ODI3%, lowest_satO2, and arousal index were also non-significant. Conclusion: No evidence for the presence of significant associations between key measures of OSA severity and cancer survival emerged, suggesting that larger studies are needed to confirm or refute this possible association. Support (If Any): This work was supported by grant number P30CA015704, R03CA201806.